Combination of Nexrutine and docetaxel suppresses NFκB‐mediated activation of c‐FLIP. Issue 10 (15th June 2017) - Zhang, Yangang; Li, Li; Wang, Jingyu; Cheng, Wei; Zhang, Jiandong; Li, Xueting; Zhang, Zhenhua; Gong, Jingjing; Ghosh, Rita; Kumar, Addanki P.; Xie, Jianping
Abstract : Lack of effective options following failure to conventional chemotherapeutic agent such as Docetaxel (DX) is a major clinical challenge in the management of prostate cancer. These observations underscore the need for deciphering the underlying mechanism of DX resistance to enable the development of effective therapeutic approaches. We observed up regulation of the anti‐apoptotic protein c‐FLIP and its up stream regulators including receptor tyrosine kinase RON and transcription factor NFκB (p65) in tumors obtained from metastatic prostate cancer patients. We also observed significant downregulation of these molecules in prostate tumors isolated from patients treated with DX as first line therapy. Further, we identified the over the counter anti‐inflammatory agent, Nexrutine (NX) suppresses c‐FLIP protein levels, and expression in androgen‐independent prostate cancer cells (PC‐3). Remarkably, the observed decreased levels of c‐FLIP were further reduced in combination with DX. Transient expression assays coupled with electrophoretic mobility shift and DNA affinity protein assay revealed that NX and DX suppresses c‐FLIP promoter activity by preventing p65 binding. Notably, NX in combination with DX abolished binding of p65 to the c‐FLIP promoter sequence containing NFκB binding sites. Biologically, these alterations resulted in reduced growth of PC‐3 cells. Taken together, these observations suggest the utility of RON, p65, and c‐FLIP as potential markers to predict response to DX treatment. Furthermore, our results also identified NX as an agent to potentiate the therapeutic response of DX by suppressing activation of c‐FLIP and its upstream regulators.